SCREENING OF DIFFERENT BT COTTON (GOSSYPIUM HIRSUTUM L.) GENOTYPES AGAINST SUCKING AND BOLLWORM COMPLEXES - Khan, M. H.; Ahmad, N.; Tofique, M. (The Nucleus, 2011)
Host plant resistance can play an important role in Integrated Pest Management (IPM) against insect pests. Relative infestation on five Bt transgenic cotton varieties/genotypes (IR-443, IR-FH-901, IR-448, IR-1524 and IR-1513) was investigated against sucking complex (jassids, thrips and whiteflies) and bollworms [pink (Pectinophora gossypiella) and spotted (Earias spp.) bollworms] during 2 consecutive years (2009 and 2010). Results reflected that IR-443 proved to be the most successful genotype rendering lowest infestation of jassids, thrips and whiteflies in both years as compared to other Bt cotton genotypes followed by IR-FH-901. Percent infestation by pink and spotted bollworms remained below Economic Threshold Level (ETL) and differed non significantly in all transgenic cotton genotypes. Highest yield was recorded from IR-443 which was significantly higher than IR-1513 and statistically at par with other three Bt cotton. Overall performance of IR-443 was found excellent followed by IR-FH-901. Thus, the latter two Bt transgenic cotton varieties/genotypes should be considered as an important tool to help in managing certain pest populations in an economically viable and environmentally safe manner.